1999
DOI: 10.1038/8780
|View full text |Cite
|
Sign up to set email alerts
|

Alymphoplasia is caused by a point mutation in the mouse gene encoding Nf-κb-inducing kinase

Abstract: The alymphoplasia (aly) mutation of mouse is autosomal recessive and characterized by the systemic absence of lymph nodes (LN) and Peyer's patches (PP) and disorganized splenic and thymic structures with immunodeficiency. Although recent reports have shown that the interaction between lymphotoxin (LT) and the LT beta-receptor (Ltbeta r, encoded by Ltbr) provides a critical signal for LN genesis in mice, the aly locus on chromosome 11 is distinct from those for LT and its receptor. We found that the aly allele … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
343
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(361 citation statements)
references
References 27 publications
17
343
0
1
Order By: Relevance
“…Although in overexpression experiments in tissue culture cells NIK acts as a potent activator of both IKK and NF-kB (Karin and Delhase, 1998;Malinin et al, 1997;Re gnier et al, 1997;Woronicz et al, 1997), recent experiments question its involvement in IKK activation by either TNFa or IL-1 . In support of these results based on transient transfection experiments, it was recently found that the aly mutation of the mouse, which results in loss of lymphoid organs, is a point mutation in the gene encoding NIK (Shinkura et al, 1999). Analysis of cells derived from aly mice indicates that IL-1 and TNFa-mediated activation of NF-kB are normal.…”
Section: Ikb Kinase and Its Regulationmentioning
confidence: 81%
See 1 more Smart Citation
“…Although in overexpression experiments in tissue culture cells NIK acts as a potent activator of both IKK and NF-kB (Karin and Delhase, 1998;Malinin et al, 1997;Re gnier et al, 1997;Woronicz et al, 1997), recent experiments question its involvement in IKK activation by either TNFa or IL-1 . In support of these results based on transient transfection experiments, it was recently found that the aly mutation of the mouse, which results in loss of lymphoid organs, is a point mutation in the gene encoding NIK (Shinkura et al, 1999). Analysis of cells derived from aly mice indicates that IL-1 and TNFa-mediated activation of NF-kB are normal.…”
Section: Ikb Kinase and Its Regulationmentioning
confidence: 81%
“…Analysis of cells derived from aly mice indicates that IL-1 and TNFa-mediated activation of NF-kB are normal. As the phenotypic appearance of aly mice is similar to that of lymphotoxin (LT)-de®cient mice (Shinkura et al, 1999), it is likely that NIK functions as a mediator of LT signaling and has no role in TNFa or IL-1 signaling. Although an interaction between NIK and IKKa was detected in yeast cells or upon overexpression of the two kinases in mammalian cells, so far it has not been detected under physiological conditions.…”
Section: Ikb Kinase and Its Regulationmentioning
confidence: 99%
“…44,45 Therefore, to assess the role of NIK in cell death of cTEC, we performed bone marrow (BM) reconstitution assays using WT or Tg Lck-LTαβ mice as donors and WT or aly/aly NIK-deficient recipient mice. 46 For phenotypic analyses, 8 weeks postreconstitution mice were killed and thymi were imaged and quantitatively and qualitatively analyzed. As previously reported, reconstitution of Lck-LTαβ BM into WT recipient mice led to a drastic reduction in thymus size compared with the reconstitution of WT BM into WT recipient mice (Figure 5a).…”
Section: Resultsmentioning
confidence: 99%
“…Mice with a point mutation in nik (aly/aly mice) lack multiple secondary lymphoid organs (Miyawaki et al, 1994;Koike et al, 1996;Shinkura et al, 1999) and share several phenotypic similarities with lymphotoxin and IKKa single knockout animals (Mebius, 2003;Bonizzi and Karin, 2004). p52/RelB, which is activated downstream of NIK and IKKa, is thought to be the primary transcriptional mediator of several key organogenic factors including CXCL12, CXCL13, CCL19, CCL21 and MadCAM-1 (Yilmaz et al, 2003).…”
Section: Secondary Lymphoid Organsmentioning
confidence: 99%